A NEW CONCEPT OF SPONDYLOARTHRITIS: A COMPROMISE BETWEEN ASAS AND GRAPPA? - Sh. F. Erdes (Научно-практическая ревматология)
The paper briefly discusses the history of spondyloarthritis (SpA) from the article published by J. Moll et al. in 1974 to the present day. The discussion of the recent SpA concept proposed by the Assessment of SpondyloArthritis International Society (ASAS), which divides this group of diseases into axial and peripheral types, by elaborating the appropriate criteria, holds a special position. This division could rapidly introduce the principles of early diagnosis of axial SpA on the one hand; however, it hinders their investigation as a genetically and clinically associated spectrum of diseases on the other hand.